Peningkatan Literasi Keuangan Melalui Efikasi Diri dan Sosial Ekonomi Orang Tua - Windi Widiawati; Khusaini; Andi Yustira L. Wahab (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2022)
Todays’ increasingly complex social and economic life requires good financial literacy knowledge and skills for all individuals. This study examines the effect of self-efficacy, socioeconomic status, and financial education on students’ financial literacy. The sample size was 98 students (10% sampling error). The sample selection technique is simple random sampling with predetermined criteria. We utilized the Logistic Binary Regression model. Research instruments distributed to samples have been tested for validity and reliability. Distribution of questionnaires utilizing google form through WhatsApp groups. The study found that students who had financial planning skills, basic understanding of macroeconomics, considerations in the use of money, saving and investment behavior, planning retirement, and analyzing risk are characteristics of financially literate students. The test results found that self-efficacy and socioeconomic status of student parents were significant determinants in improving financial literacy. On the contrary, financial education had no significant effect. This result implies that students are always able to cover their own weaknesses with strengths by understanding and changing behavior in making financial planning and decisions. Meanwhile, rational financial decisions in the family should be known by their children and involve them.